Diagnostic challenges of nonodontogenic toothache - Hyung-Ok Park; Jung-Hong Ha; Myoung-Uk Jin; Young-Kyung Kim; Sung-Kyo Kim (Korean Academy of Conservative Dentistry, 2012)
The objective of this article was to present two nonodontogenic conditions that may mimic odontogenic toothache: trigeminal neuralgia and burning mouth syndrome. Two cases are presented in which one is related to the upper left second premolar and the other is related to the upper left first molar. Both showed pain when chewing. These two cases highlight the complexities involved in diagnosing nonodontogenic toothache. This article demonstrates the importance of having a thorough knowledge of both odontogenic and nonodontogenic toothache, as well as the need for careful evaluation of the nature of the pain and history, clinical and radiographic examinations.